2021
DOI: 10.1007/s00431-021-04235-4
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 in children: clinical and epidemiological spectrum in the community

Abstract: Most publications on pediatric COVID-19 in Spain were performed at the beginning of the pandemic when some diagnostic tools were not widely available. This study aims to show the real spectrum of the infection based on wide detection of cases due to symptoms and contact tracing. A descriptive and analytical observational study was performed including pediatric cases (0 to 14 years) from the region of Aragón between May 12 and October 31, 2020. Diagnostics was by PCR detection of viral RNA, rapid antigen detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
(33 reference statements)
5
14
0
1
Order By: Relevance
“…Our study, conducted in a very large sample in the community, confirms what has been described in previous publications 4 , 5 , 16 , 17 : in the paediatric population, COVID-19 is a mild and oligosymptomatic disease in the community. The salient findings were the frequent presentation with rhinorrhoea, which is not a symptom included in reference protocols 18 ; its presence should be taken into account, despite its nonspecificity (frequent in infants, associated with allergic processes…), depending on the current epidemiological context.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study, conducted in a very large sample in the community, confirms what has been described in previous publications 4 , 5 , 16 , 17 : in the paediatric population, COVID-19 is a mild and oligosymptomatic disease in the community. The salient findings were the frequent presentation with rhinorrhoea, which is not a symptom included in reference protocols 18 ; its presence should be taken into account, despite its nonspecificity (frequent in infants, associated with allergic processes…), depending on the current epidemiological context.…”
Section: Discussionsupporting
confidence: 91%
“…One of the greatest challenges in fighting this disease is the presence of asymptomatic patients and their ability to spread the infection. 22 , 23 , 24 The first studies published during the pandemic, when diagnostic tests were only available in the hospital setting, the proportion of asymptomatic patients in the paediatric population was reported to be as low as 14% 15 ; since then, other studies using data obtained in the community and from population screening found percentages of 35%–50% 13 , 17 , 25 , 26 and even as high as 71%–76.5% in the case of studies that only assessed symptoms at the time of diagnosis. 27 , 28 In our study, in which a follow-up assessment of symptoms was conducted at 15 days, the percentage of asymptomatic patients was 43%.…”
Section: Discussionmentioning
confidence: 99%
“…22 Compared with the few previous studies providing population based data on the risk of hospital admission after SARS-CoV-2 infection, the reported risks were similar to those of Israel and Spain (0.2% to 0.5%), but lower than those reported from the UK (1.3%) and US (5.7%). 7 23 24 25 Both the case fatality rate and the risk of hospital admissions are, however, influenced by access to testing for SARS-CoV-2 and are likely to be overestimates of the true risk. Recent Danish SARS-CoV-2 seroprevalence studies have estimated that the true prevalence of SARS-CoV-2 infection among adolescents is up to threefold higher than that detected by national RT-PCR tests.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Studies have, however, consistently reported that SARS-CoV-2 infection in children and adolescents is generally asymptomatic or mild, limiting the benefit of vaccination in individual. 7 …”
Section: Introductionmentioning
confidence: 99%
“…In our current study, housewife and nulliparous women were less likely to have COVID-19. Children have oligosymptomatic COVID-19 and may be potential vectors to the adult population [21]; that is why women without children could be less exposed to acquiring the disease. Similarly, women who remain at home have less chance of being in contact with infected people.…”
Section: Discussionmentioning
confidence: 99%